2009
DOI: 10.5194/angeo-27-303-2009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic activity on plasma bubbles over equatorial and low-latitude regions in East Asia

Abstract: Abstract. The dependence of plasma bubble occurrence in the eveningside ionosphere, with magnetic activity during the period years [2001][2002][2003][2004], is studied here based on the TEC observations gathered by ground-based GPS receivers which are located in the equatorial and low-latitude regions in East Asia. The observed plasma bubbles consist of the plasma-bubble events in the equatorial (stations GUAM, PIMO and KAYT), and low-latitude regions (stations WUHN, DAEJ and SHAO). It is shown that most equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 34 publications
1
57
0
1
Order By: Relevance
“…Our results show seasonal and longitudinal variation in agreement with those of past studies which employed ground and satellite-based measurements (Basu and Basu 1985;Aarons 1993;Kil and Heelis 1998;Burke et al 2000;Huang et al 2001;Burke et al 2004aBurke et al , 2004bGentile et al 2006;Li et al 2009). The typical categories of the DMSP observed EPBs during 2005 falls mainly under M-0 and M-1.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results show seasonal and longitudinal variation in agreement with those of past studies which employed ground and satellite-based measurements (Basu and Basu 1985;Aarons 1993;Kil and Heelis 1998;Burke et al 2000;Huang et al 2001;Burke et al 2004aBurke et al , 2004bGentile et al 2006;Li et al 2009). The typical categories of the DMSP observed EPBs during 2005 falls mainly under M-0 and M-1.…”
Section: Discussionsupporting
confidence: 94%
“…Huang et al (2001) have shown that EPB activity in the evening sector is enhanced during the early stages of high geomagnetic activity but can be suppressed, sometimes for days, after prolonged elevated activity. Based on the Dynamics Explorer (DE) 2 satellite observations from August 1981 to February 1983, Palmroth et al (2000 investigated the occurrence of EPBs and found that magnetic activity appears to suppress the generation of evening side plasma bubbles with a delay of 2-5 h. Recently, Li et al (2009) studied the dependence of EPB occurrence in the evening side ionosphere, with magnetic activity based on the TEC observations gathered by ground-based GPS receivers located in East Asia and found that the magnetic activity appears to suppress the generation of EPBs with a time delay of more than 3 h (4-9 h).…”
Section: Introductionmentioning
confidence: 99%
“…However, geomagnetic activity (Kp ≥ 3) has been linked to postmidnight plasma bubble formation that can give rise to UHF scintillation at 0300 LT [Palmroth et al, 2000;Huang et al, 2005;Li et al, 2009]. Therefore, the geomagnetic conditions during Operation Anaconda are relevant to an assessment of the SATCOM outages experienced after 0300 LT on 4 Mar 2002.…”
Section: Space Weather Conditionsmentioning
confidence: 99%
“…Moreover, almost all of statistical studies show that MSTIDs are common 978-1-4244-6051-9/11/$26.00 ©2011 IEEE e region between equator and mid-latitudes, and closes t egion. Some studies directly and indirectly point out tha is region [2,3]. In this study, we investigated the occurren at nighttime in 2000.…”
Section: Introductionmentioning
confidence: 98%